Citizenship Education in Early Republican Era in Turkey - Mehmet Melik Kaya (Research in Social Sciences and Technology- OpenED Network, 2022)
In Turkey, the Republican Era, which started in 1923, is a period in which state institutions were rapidly restructured and these institutions were reconstituted within the framework of the ideology of the newly established state. Education has taken its share in this reconstruction process as well. One of the important regulations in the field of education was the 1924 curriculum. The 1924 curriculum was quite important in terms of reflecting the Republic’s perspective on education and the importance it attaches to education. Through this curriculum, it was aimed to raise patriotic individuals who are loyal to the philosophy and values of the Republic, have national consciousness, and understand the new state, institutions and organizations. The aim of the research is to examine the first citizenship education course of the Republic of Turkey, Musâhabât-ı Ahlâkiyye & Malumât-ı Vataniye [Conversations on Morality and Civics], which was included in the 1924 educational program. In the study, this curriculum was analyzed by employing the historical research method. Keywords: History of education, citizenship education, 1924 curriculum, republican era, historical research